PENGEFORMER BLANDT FATTIGE FORBRUGERE I DANMARK - Hohnen, Pernille (Tidsskriftet Antropologi, 2018)
The first half of the article presents critical analyses of the existing “consensus” within consumption studies, namely that consumption is primarily about symbolism, freedom of choice and lifestyle, by introducing dissenting voices (Carrier & Heyman; Löfgren; and Lodziak) arguing for a revival of a more political-economic framework. The author proceeds to argue that by using a broader framework of both qualitative and quantitative money (Zelizer), it is possible to focus on the interplay between material and immaterial dimensions at work in contemporary processes of social differentiation. The second half of the article consists of an empirical analysis of consumption patterns and forms of money in poor Danish families. This reveals a widespread tendency among the poor families to earmark the limited amount of money available with the result that they have no “free money” at all. The earmarking is a way to control money according to different principles, e.g. use value, temporality, beneficiaries of pursuits (children/ parents), material form (electronic money versus paper money) and moral discourses. The tendency to conceptualise money in terms of qualitatively different currencies, however, also places poor citizens in a position outside mainstream consumption regimes, in contrast to existing discourses on consumption in contemporary Danish society.